Safety, tolerability, efficacy and pharmacodynamics of the selective JAK1 inhibitor GSK2586184 in patients with systemic lupus erythematosus. (November 2016) - Kahl, L; Patel, J; Layton, M; Binks, M; Hicks, K; Leon, G; Hachulla, E; Machado, D; Staumont-Sallé, D; Dickson, M; Condreay, L; Schifano, L; et al.
We aimed to evaluate the pharmacodynamics, efficacy, safety and tolerability of the JAK1 inhibitor GSK2586184 in adults with systemic lupus erythematosus (SLE). In this adaptive, randomized, double-blind, placebo-controlled study, patients received oral GSK2586184 50–400 mg, or placebo twice daily for 12 weeks. Primary endpoints included interferon-mediated messenger RNA transcription over time, changes in Safety of Estrogen in Lupus National Assessment-SLE Disease Activity Index score, and number/severity of adverse events. A pre-specified interim analysis was performed when ≥ 5 patients per group completed 2 weeks of treatment. In total, 84–92% of patients were high baseline expressors of the interferon transcriptional biomarkers evaluated. At interim analysis, GSK2586184 showed no significant effect on mean interferon transcriptional biomarker expression (all panels). The study was declared futile and recruitment was halted at 50 patients. Shortly thereafter, significant safety data were identified, including elevated liver enzymes in six patients (one confirmed and one suspected case of Drug Reaction with Eosinophilia and Systemic Symptoms), leading to immediate dosing cessation. Safety of Estrogen in Lupus National Assessment-SLE Disease Activity Index scores were not analysed due to the small number of patients completing the study. The study futility and safety data described for GSK2586184 do not support further evaluation in patients with SLE. Study identifiers: GSK Study JAK115919; ClinicalTrials.gov identifier: NCT01777256.